One-pot preparation of nano-scaled magnetic-pectin particles (Fe3O4@pectin NPs): cytotoxicity, antioxidant, and anti-liver cancer properties. Issue 1 (31st December 2022) - Zhang, Qiao; Cui, Wenyu; Guo, Honglin; Wang, Baoqing; Wang, He; Zhang, Jimei; Li, Wenlan
Abstract: This work described the one-pot synthesis of orange pectin encapsulated Fe3O4 nanoparticles (Fe3 O4 @Pectin NPs) which is prepared by co-precipitation of Fe(II/(III) ions in alkaline solution mediated by pectin. This process led to formation of magnetic nanoparticles within the network of pectin. Physicochemical characterization of the as-synthesized Fe3 O4 @Pectin NPs was carried out through Fourier transformed infrared spectroscopy (FT-IR), electron microscopy (SEM and TEM), energy dispersive X-ray spectroscopy (EDX), vibrating sample magnetometer (VSM) and X-ray diffraction (XRD). The in vitro cytotoxic and anti-liver cancer effects of biologically synthesized Fe3 O4 @Pectin NPs against pleomorphic hepatocellular carcinoma (SNU-387), hepatic ductal carcinoma (LMH/2A), morris hepatoma (McA-RH7777), and novikoff hepatoma (N1-S1 Fudr) cancer cell lines were assessed. The anti-liver cancer properties of the Fe3 O4 @Pectin NPs could significantly remove pleomorphic hepatocellular carcinoma (SNU-387), hepatic ductal carcinoma (LMH/2A), morris hepatoma (McA-RH7777), and novikoff hepatoma (N1-S1 Fudr) cancer cell lines in a time and concentration-dependent manner by MTT assay. The IC50 of the Fe3 O4 @Pectin NPs were 8, 13, 10, and 7 µg/mL against pleomorphic hepatocellular carcinoma (SNU-387), hepatic ductal carcinoma (LMH/2A), morris hepatoma (McA-RH7777), and novikoff hepatoma (N1-S1 Fudr) cancer cell lines. The antioxidant activity of Fe3 O4 @Pectin NPs was determined by DPPH method. The Fe3 O4 @Pectin NPs showed the high antioxidant activity according to the IC50 value. It seems that the anti-human liver cancer effect of recent nanoparticles is due to their antioxidant effects.